Wintersmith / 3. - Pratchett, Terry, 1948-2015 (Tiffany Aching - Discworld, 2006)
Witch-in-training Tiffany Aching accidentally interrupts the Dance of the Seasons and awakens the interest of the elemental spirit of Winter, forcing her to turn to the six-inch-high, sword-wielding, sheep-stealing Wee Free Men to put the seasons aright.